2021
DOI: 10.3174/ajnr.a7281
|View full text |Cite
|
Sign up to set email alerts
|

SWI Susceptibility Vessel Sign in Patients Undergoing Mechanical Thrombectomy for Acute Ischemic Stroke

Abstract: BACKGROUND AND PURPOSE:The frequency and clinical significance of the susceptibility vessel sign in patients with acute ischemic stroke remains unclear. We aimed to assess its prevalence in patients with acute ischemic stroke undergoing mechanical thrombectomy and to analyze its association with interventional and clinical outcome parameters in that group.MATERIALS AND METHODS: Six hundred seventy-six patients with acute ischemic stroke and admission MR imaging were reviewed retrospectively. Of those, 577 met … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…Between January 2010 and December 2018, 1,317 patients with AIS were treated with MT at our stroke center. As already described by Belachew et al and shown in Supplementary Figure I (study flowchart), 577 patients had SWI with assessable SVS status available at admission and met the inclusion criteria ( 24 ). Evidence of active malignancy at the time of stroke was found in 40 patients (6.93%), of which a subset of 9 patients (1.56%) had occult malignancy.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Between January 2010 and December 2018, 1,317 patients with AIS were treated with MT at our stroke center. As already described by Belachew et al and shown in Supplementary Figure I (study flowchart), 577 patients had SWI with assessable SVS status available at admission and met the inclusion criteria ( 24 ). Evidence of active malignancy at the time of stroke was found in 40 patients (6.93%), of which a subset of 9 patients (1.56%) had occult malignancy.…”
Section: Resultsmentioning
confidence: 99%
“…Magnetom Verio 3T SWI was performed with the following parameters: TR, 27 ms; TE, 20 ms; flip angle, 15.0°; section thickness, 2.0 mm; and intersection gap, 0 mm. The detailed method used to determine the presence of SVS in the cohort analyzed in this article was described by N. Belachew et al in a previous publication ( 24 ). To summarize, SVS status was assessed retrospectively by two independent neuroradiologists (N.F.B.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most previous susceptibility-related MRI studies focused on the image signs like SVS ( Belachew et al, 2021 , Bourcier et al, 2015 , Bourcier et al, 2018 , Cho et al, 2005 , Darcourt et al, 2019 , Kang et al, 2017 , Liu et al, 2019 , Soize et al, 2015 ) due to the easy clinical availability. The present study is one of the first studies to explore the thrombus properties and outcome associations by the quantification MRI method.…”
Section: Discussionmentioning
confidence: 99%
“…The MRI susceptibility vessel sign (SVS), defined as the hypointense blooming signals on T2*-weighted or susceptibility-weighted imaging (SWI), demonstrates the existence of local paramagnetic contents such as deoxyhemoglobin and methemoglobin ( Cho et al, 2005 ). Many studies reported that patients with SVS receiving EVT were more likely to recanalize and improve clinical outcomes ( Belachew et al, 2021 , Bourcier et al, 2015 , Bourcier et al, 2018 , Darcourt et al, 2019 , Liu et al, 2019 ). However, on the same issue, several studies showed negative results ( Soize et al, 2015 , Kang et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%